Tenderness and the Calpain System of Three Different Types of Muscles of Kejobong Does under Two Different Energy Levels - Socheh, M; Ismaya, Ismaya; Budisatria, I Gede Suparta; Kustantinah, Kustantinah (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. The purpose of research was to investigate whether there was influence of the addition of concentrates in basal feed on meat tenderness and calpastatin and calpain activities of three muscles of Kejobong does. A total of 20 heads of Kejobong does (2.0-2.5 years) with initial live weight range between 23.8-24.2 kg was studied and randomly set in two kinds of feed treatment, ie basal feed (p0) and basal feed plus concentrates (p1). Two kinds of feed were given to Kejobong doe for 12 weeks. The observed variables were (1) tenderness of meat, (2) calpain activity (m-calpain activity and the activity of m-calpain), and (3) calpastatin activity. Data were processed using the General Linear Model Univariate procedure and Pearson Bivariate Correlation of the SPSS program. Results showed that feeding (basal feed and basal feed plus concentrates) significantly affected meat tenderness of Kejobong doe. The types of muscles had highly significant effect on tenderness. Feeds affected m-calpain activity, m-calpain activity, and calpastatin activity in the muscles. Types of muscles exhibited variation in the activity of m-calpain, the activity of m-calpain, and calpastatin activity. In conclusion, the addition of concentrates in the basal feed increased meat tenderness, and affected the activity of m-calpain, m-calpain, and calpastatin.Keywords: activity of m-calpain and m-calpain, calpastatin activity, Kejobong doeAnimal Production 14(1):47-55, January 2012